A method for predicting the critical solidification period of crystal grains.

By establishing a database of CHS crystal bridge growth model and using empirical formula calculations, the problems of time-consuming, high cost and poor accuracy of predicting the key aggregation period of crystal particles in the prior art are solved, and a fast, accurate and low-cost prediction effect is achieved.

JP7669002B2Active Publication Date: 2025-04-28TIANJIN UNIV +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024539443
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-20
Filing Date
2023-07-06
Publication Date
2025-04-28
Estimated Expiration
2043-07-06

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately predict the critical aggregation period of crystal particles, and the experiment volume is large and the cost is high, making it difficult to adapt to different temperature and humidity conditions.

Method used

Establish a database of CHS crystal bridge growth models, and use specific empirical formulas to calculate and predict the key aggregation period of crystal particles by comparing the equivalent particle size of crystal particles with the temperature and humidity conditions of the storage environment.

Benefits of technology

The critical aggregation period of crystal particles is achieved quickly, accurately, low experimental volume and low cost prediction, which is suitable for the prediction of a variety of crystal particles products under different humidity storage conditions, significantly reducing time costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669002000004
    Figure 0007669002000004
  • Figure 0007669002000005
    Figure 0007669002000005
  • Figure 0007669002000006
    Figure 0007669002000006
Patent Text Reader

Abstract

The present invention belongs to the technical field of aggregation and consolidation of crystal particles, and relates to a method for predicting the critical consolidation period of crystal particles. The method of the present invention includes the steps of first creating a CHS crystal bridge growth model database of crystal particles of the same type as the prediction target crystal particles, and then selecting existing data in the corresponding CHS crystal bridge growth model database according to the equivalent particle radius of the prediction target crystal particles, the storage environmental temperature, and the environmental high and low humidity cycle conditions, calculating the critical consolidation period by an empirical calculation formula, and obtaining the predicted critical consolidation period of the crystal particles as the calculation result. The present invention has the characteristics of time-saving, convenience, high versatility, high prediction accuracy, etc., and can quickly predict the critical consolidation period of multi-grain crystal particle products under various humidity storage conditions within a maximum of one week, greatly reducing time and cost, and providing a basis for guidance on the storage of industrial crystal particle products.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of aggregation and consolidation of crystal particles, and in particular to a method for predicting the critical consolidation period of crystal particles. [Background technology]

[0002] The caking of crystal particles is a process in which crystal particles that are originally good in fluidity and dispersibility aggregate together to form irregular aggregates. The caking phenomenon of crystal particles is very likely to occur during the post-processing of crystal products (transportation, storage, and drying of crystals), which leads to a decrease in the usability of the crystal particle products. Therefore, in order to guide the growth, storage, transportation, etc. of crystal particle products, it is important to measure the critical caking period of crystal particle products under various temperature and humidity storage conditions and predict the critical caking period.

[0003] However, currently, the prediction of the critical consolidation period of crystal grains is mainly realized based on establishing the corresponding relationship between the high temperature and high humidity accelerated consolidation experiment process under laboratory conditions and the consolidation rate under actual storage environment, the whole experiment period is relatively long (requiring several months to a year), and the amount of experiment is large, and one experiment can only measure the critical consolidation period under a specific humidity cycle condition, and it is not possible to realize rapid and accurate prediction of particle groups under various temperature and humidity conditions. In addition, the critical consolidation period of crystal grains shows a high correlation with the size of the grain itself, and the current general understanding is that the larger the grain size, the longer the critical consolidation period, but a quantitative mathematical relationship that realizes theoretical guidance of the consolidation process has not been established.

[0004] Therefore, it is an important and urgent task to explore a method for predicting the critical solidification period of crystalline grain products that is rapid, accurate, requires less experimentation, and has low overall cost. Summary of the Invention [Problem to be solved by the invention]

[0005] The technical problem to be solved by the present invention is to provide a method for predicting the critical solidification period of crystal grains, which is characterized by being fast and accurate, requiring less experimentation, and requiring low overall cost, in order to solve the conventional defects such as the time-consuming testing of the critical solidification period of crystal grain products, the large amount of measurement work, the difficulty of prediction, and the high cost. [Means for solving the problem]

[0006] The present invention is achieved as follows: A method for predicting the critical solidification period of a crystal particle, comprising the steps of: first, creating a CHS crystal bridge growth model database of crystal particles of the same kind as the prediction target crystal particle, including data on equivalent particle radii corresponding to various particle size standards of the crystal particles, data on moisture absorption amounts of crystal particles of various equivalent particle radii under various environmental temperatures and various environmental humidity conditions, and data on the critical solidification periods of crystal particles of various equivalent particle radii under various environmental temperatures and various environmental high-low humidity cycle conditions; then, selecting existing data in the corresponding CHS crystal bridge growth model database according to the equivalent particle radius, storage environmental temperature, and environmental high-low humidity cycle conditions of the prediction target crystal particle, calculating the critical solidification period according to the following formula, and obtaining the predicted critical solidification period for this crystal particle as the calculation result; The formula includes the following: (1) When the environmental temperature and environmental high-low humidity cycle conditions of the prediction target crystal grain are the same as the data in the CHS crystal bridge growth model database and only the equivalent particle radius is different, calculate the critical solidification period N1' of the prediction target crystal grain under the environmental conditions according to the following formula (a); N1 / N1'=(R 1e / R 1e ') 4 , formula (a) In the above formula, R 1e is the equivalent grain radius of the existing crystal grain in the CHS crystal bridge growth model database, and R 1e ' is the equivalent particle radius of the crystal grain to be predicted, and N1 is the equivalent particle radius R 1eN1' is the critical solidification period of the crystal grain corresponding to the environmental conditions, N1' is the critical solidification period of the prediction target crystal grain, and N1 and N1' are each integers equal to or greater than 1; (2) When the environmental temperature and equivalent particle radius of the prediction target crystal grain are the same as those in the CHS crystal bridge growth model database, and only the environmental high-low humidity cycle conditions are different, calculate the critical solidification period N2'' of the prediction target crystal grain according to the following formula (b): N2 / N2''=V l ' / V l , formula (b) Where: V l =V RH2 -V RH1 , formula (c) V l '=V RH3 -V RH1 , formula (d) In the above formula, V RH2 is the amount of moisture absorbed under high humidity conditions in the first environmental high-low humidity cycle of a crystal grain existing in the CHS crystal bridge growth model database, and V RH3 is the amount of moisture absorbed by the existing crystal grains in the CHS crystal bridge growth model database under high humidity conditions in the second environment high-low humidity cycle, and the low humidity conditions in the first environment high-low humidity cycle and the second environment high-low humidity cycle are the same. V RH1 is the amount of moisture absorbed under low humidity conditions in the high and low humidity cycle of the crystal grains existing in the CHS crystal bridge growth model database, and V l is the difference in moisture absorption of the crystal grains under the first environmental high and low humidity cycle conditions, and V l N' is the moisture absorption difference of the crystal grain to be predicted under the high and low humidity cycle condition of the second environment, N2 is the critical solidification period of the crystal grain existing in the CHS crystal bridge growth model database under the high and low humidity cycle condition of the first environment, N2'' is the critical solidification period of the crystal grain to be predicted under the high and low humidity cycle condition of the second environment, N2 and N2'' are each an integer of 1 or more, The present invention provides a method for predicting the critical solidification period of crystal particles, in which the high humidity condition in the environmental high and low humidity cycle is lower than the deliquescence point of the crystal particles, the critical solidification period when the particle diameter of the crystal particles is less than 100 microns is greater than one, the low humidity condition is lower than the high humidity condition, and the humidity difference between the two is greater than 20%.

[0007] Furthermore, the equivalent particle radius of the crystal grain in the CHS crystal bridge growth model database and the equivalent particle radius of the prediction target crystal grain are, respectively, First, the grain size of the crystal grain product to be measured is selected, and then the mass of the crystal grains for each grain size range is measured and the data m1, m2, ..., m n At the same time, the number of crystal grains in each grain size range is counted, and the data P1, P2, ..., P n Then, the equivalent particle radius R of the crystal grain is calculated by the following formula. e The formula is: P1R1 3 +P2R2 3 +…+P n R n 3 =(P1+P2+…+P n )R e 3 , formula (e) P1R1 3 :P2R2 3 :…:P n R n 3 =m1:m2:…:m n , including formula (f).

[0008] Furthermore, the critical solidification period of the crystal grains having various equivalent particle radii at various environmental temperatures and various environmental high and low humidity cycles is First, the crystal particle product to be measured is filled into a consolidation mold and placed in a box with a set temperature. The high and low humidity of the high and low humidity cycle in the box are set to match the environmental high and low humidity cycle of the crystal particles to be measured. The period of the high and low humidity cycle is set to 12 to 24 hours. Then, timing of the high and low humidity cycle is started. Each time a high and low humidity cycle period is completed, the solidified body in the consolidation mold is released. If the solidified body of the crystal particles collapses upon release, it is determined that the crystal particle product is not solidified. The cycle is continued until the next period. When the solidified body of the crystal particles no longer collapses, the number of periods until the solidified body no longer collapses is recorded, and this is determined to be the critical consolidation period for the crystal particles under the environmental temperature and environmental high and low humidity cycle conditions.

[0009] Furthermore, when measuring the critical solidification period, the critical solidification period is measured three times, and the average value of the critical solidification periods measured three times is taken as the averaged critical solidification period.

[0010] Furthermore, V in formulas (c) and (d) RH1 , V RH2 and V RH3 is also calculated by the following method: Under the same environmental temperature, same environmental humidity, and different equivalent particle radii, the equivalent particle radius R is calculated by the following formula (g). e The amount of moisture absorbed by crystal particles under environmental humidity RH conditions V RH ', V RH / V RH '=R e / R e ', formula (g) In the above formula, V RH is the equivalent particle radius R existing in the CHS crystal bridge growth model database. e is the amount of moisture absorbed by the crystal grains under the environmental humidity RH condition, and V RH ' is V RH1 , V RH2 and V RH3 It corresponds to one of the following:

[0011] Furthermore, the moisture absorption amount of the crystal particles is measured using a dynamic vapor adsorption apparatus, an initial drying process is performed on the crystal particle sample to be measured prior to the measurement, and the mass of the crystal particle sample to be measured is 10 mg or less.

[0012] Furthermore, in the environmental high and low humidity cycle of the xylitol crystal particles, the high humidity condition is 65% and the low humidity condition is 30%. Effect of the Invention

[0013] Compared with the prior art, the method for predicting the critical solidification period of crystal grains of the present invention includes the steps of firstly creating a CHS crystal bridge growth model database of crystal grains of the same type as the crystal grains to be predicted, then selecting existing data in the corresponding CHS crystal bridge growth model database according to the equivalent particle radius of the crystal grains to be predicted, the storage environmental temperature and the environmental high and low humidity cycle conditions, calculating the critical solidification period by an empirical calculation formula, and obtaining the predicted critical solidification period of the crystal grains as the calculation result. The present invention has the characteristics of time-saving, convenience, high versatility, high prediction accuracy, etc., and can quickly predict the critical solidification period of multi-grain crystal grain products under various humidity storage conditions within a maximum of one week, greatly reducing time and cost, and providing a basis for guidance on the storage of industrial crystal grain products. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic cross-sectional view of the structure of a consolidation mold used in measuring the critical consolidation period of the present invention. [Diagram 2]Schematic diagrams showing a comparison between the predicted results calculated based on the moisture absorption file of the xylitol crystal particle product in Example 1 of the present invention and the CHS crystal bridge growth model database and the actual measured results, where (a) is a moisture absorption curve of a xylitol crystal particle at a temperature of 25°C, (b) is a schematic diagram showing a comparison between the predicted results and the actual measured results between the moisture absorption amount and equivalent particle radius of a xylitol crystal particle, (c) is a schematic diagram showing a comparison between the predicted results and the actual measured results between the critical solidification period and moisture absorption amount difference of a xylitol crystal particle, and (d) is a schematic diagram showing a comparison between the predicted results and the actual measured results between the critical solidification period and equivalent particle radius of a xylitol crystal particle. [Diagram 3] FIG. 2 is a fitting schematic diagram showing the predicted critical caking period of the multi-particle crystal product of xylitol crystal particles in Example 1 of the present invention under various humidity storage conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In order to make the technical problems, technical solutions and beneficial effects of the present invention clearer and more obvious, the present invention will be described in more detail below with reference to the drawings and examples. It should be understood that the specific examples described in this specification are only used to explain the present invention and are not used to limit the present invention.

[0016] In a preferred embodiment of the method for predicting the critical solidification period of a crystal particle of the present invention, the method first includes the steps of creating a CHS crystal bridge growth model database of crystal particles of the same type as the crystal particle to be predicted, the database including data on equivalent particle radii corresponding to various particle size standards of the crystal particles, data on moisture absorption amounts of crystal particles of various equivalent particle radii under various environmental temperature and various environmental humidity conditions, and data on critical solidification periods of crystal particles of various equivalent particle radii under various environmental temperature and various environmental high-low humidity cycle conditions, and then selecting existing data in the corresponding CHS crystal bridge growth model database according to the equivalent particle radius, storage environmental temperature, and environmental high-low humidity cycle conditions of the crystal particle to be predicted, calculating the critical solidification period according to the following calculation formula, and obtaining the predicted critical solidification period for this crystal particle as the calculation result.

[0017] The formula includes the following: (1) When the environmental temperature and environmental high-low humidity cycle conditions of the prediction target crystal grain are the same as the data in the CHS crystal bridge growth model database and only the equivalent particle radius is different, calculate the critical solidification period N1' of the prediction target crystal grain under the environmental conditions according to the following formula (a); N1 / N1'=(R 1e / R 1e ') 4 , formula (a) In the above formula, R 1e is the equivalent grain radius of the existing crystal grain in the CHS crystal bridge growth model database, and R 1e ' is the equivalent particle radius of the predicted crystal grain, and N1 is the equivalent particle radius R 1e N1 is the critical solidification period of the crystal grain corresponding to the environmental conditions, and N1' is the critical solidification period of the prediction target crystal grain. N1 and N1' are each an integer of 1 or more.

[0018] (2) When the environmental temperature and equivalent particle radius of the predicted crystal grain are the same as the data in the CHS crystal bridge growth model database, and only the environmental high-low humidity cycle conditions are different, the critical solidification period N2'' of the predicted crystal grain is calculated using the following equation (b). N2 / N2''=V l ' / V l , formula (b) Where: V l =V RH2 -V RH1 , formula (c) V l '=V RH3 -V RH1 , formula (d) In the above formula, V RH2 is the amount of moisture absorbed under high humidity conditions in the first environmental high-low humidity cycle of a crystal grain existing in the CHS crystal bridge growth model database, and V RH3 is the amount of moisture absorbed by the crystal grains existing in the CHS crystal bridge growth model database under high humidity conditions in the second environment high-low humidity cycle. The low humidity conditions in the first environment high-low humidity cycle and the second environment high-low humidity cycle are the same, and V RH1 is the amount of moisture absorbed under low humidity conditions in the high and low humidity cycle of crystal grains existing in the CHS crystal bridge growth model database. V l is the difference in moisture absorption of the crystal grains under the first environmental high and low humidity cycle conditions, and V l N' is the moisture absorption difference of the crystal particle to be predicted under the high and low humidity cyclic conditions in the second environment, N2 is the critical solidification period of the crystal particle existing in the CHS crystal bridge growth model database under the high and low humidity cyclic conditions in the first environment, and N2'' is the critical solidification period of the crystal particle to be predicted under the high and low humidity cyclic conditions in the second environment. N2 and N2'' are each an integer of 1 or more.

[0019] In the environmental high and low humidity cycle, the high humidity condition is lower than the deliquescence point of crystal particles, and the critical solidification period when the particle size of crystal particles is less than 100 microns is greater than one time, and the low humidity condition is lower than the high humidity condition, and the humidity difference between them is greater than 20%.For example, when the deliquescence point of xylitol crystal particles is 75%, in the environmental high and low humidity cycle of xylitol crystal particles, the optimal high humidity condition is 65%, and the optimal low humidity condition is 30%.

[0020] The equivalent particle radius of the crystal grain in the CHS crystal bridge growth model database and the equivalent particle radius of the prediction target crystal grain are, respectively, First, the grain size of the crystal grain product to be measured is selected, and the crystal grain product is sorted with a metal sieve of the corresponding micron size according to the grain size and grain size distribution characteristics. Then, the mass of the crystal grains for each grain size range is measured, and data m1, m2, ..., m n At the same time, the number of crystal grains in each grain size range is counted, and the data P1, P2, ..., P n Then, the equivalent particle radius R of the crystal grain is calculated by the following formula. e The formula is: P1R1 3 +P2R2 3 +…+P n R n 3 =(P1+P2+…+P n )R e 3 , formula (e) P1R1 3 :P2R2 3 :…:P n R n 3 =m1:m2:…:m n , including formula (f). Specifically, the critical solidification periods of crystal grains having various equivalent grain radii at various environmental temperatures and various environmental high and low humidity cycles are obtained as follows.

[0021] First, the crystal particle product to be measured is filled into a consolidation mold and placed in a box with a set temperature. The high and low humidity of the high and low humidity cycle in the box are set to match the environmental high and low humidity cycle of the crystal particles to be measured, and the humidity change under the actual storage conditions of the crystal particles is simulated. The crystal particles are dissolved and recrystallized to form a crystal bridge. The period of the high and low humidity cycle is set to 12 to 24 hours, thereby ensuring the moisture absorption balance of the crystal particles. Then, the timing of the high and low humidity cycle is started. Each time the high and low humidity cycle period is completed, the solidified body in the consolidation mold is released. In the demolding, it is determined that the solidified body of the crystal particles has collapsed and the crystal particle product is not solidified, and the cycle is continued until the next period. When the solidified body of the crystal particles does not collapse, the number of periods until the solidified body does not collapse is recorded, and this is regarded as the critical consolidation period of the crystal particles under the environmental temperature and environmental high and low humidity cycle conditions.

[0022] In practical use, the box is a temperature and humidity controlled box.

[0023] The above method is suitable for measuring the critical solidification period in the CHS crystal bridge growth model database as well as for verifying the critical solidification period of the prediction target.

[0024] When measuring the critical solidification period, the critical solidification period is measured three times, and the average value of the three critical solidification periods is taken as the averaged critical solidification period.

[0025] Specifically, as shown in FIG. 1, it is a cross-sectional schematic diagram of the structure of the solidification mold used in the present invention. The solidification mold includes a base 1, a cylindrical container 2 arranged vertically on the base 1, and a fixed sleeve 3 provided on the outer periphery of the container 2 and easily attached and detached. The container 2 includes a left case and a right case for facilitating demolding, and the fixed sleeve 3 connects the left case and the right case to form the container 2. The crystal particle product J to be measured is contained in the container 2, and a plurality of vent holes (not shown) are provided on each of the side walls of the container 2. The inner diameter of each vent is smaller than the particle diameter of the crystal particles. A pressurizing block 4 is provided on the top of the crystal particle product, and a weight 5 is provided on the top of the pressurizing block. Both the pressurizing block 4 and the weight 5 pressurize and compress the crystal particles in the container 2 to make them into a solidified body. When demolding the crystal particle solidified body in the container 2, further stress is applied to the solidified body, which is crushed and collapsed, and it is necessary to avoid erroneous judgment of the solidification period.

[0026] In formulas (c) and (d), V RH1 , V RH2 and V RH3 is also calculated by the following method. Under the conditions of the same environmental temperature, the same environmental humidity, and different equivalent particle radii, the equivalent particle radius R is calculated by the following formula (g). e The amount of moisture absorbed by crystal particles under environmental humidity RH conditions V RH ' to calculate. V RH / V RH '=R e / R e ', formula (g) In the above formula, V RH is the equivalent particle radius R existing in the CHS crystal bridge growth model database. e is the amount of moisture absorbed by the crystal grains under the environmental humidity RH condition, and V RH ' is V RH1 , V RH2 and V RH3 It corresponds to one of the following:

[0027] The moisture absorption amount of the crystal particles is measured using a dynamic vapor adsorption apparatus, and an initial drying process is carried out on the crystal particle sample to be measured prior to the measurement, and the mass of the crystal particle sample to be measured is 10 mg or less.

[0028] The method for predicting the critical solidification period of crystal grains according to the present invention will be further illustrated below by specific examples. Example 1

[0029] A first embodiment of the method for predicting the critical solidification period of a crystal grain according to the present invention includes the following steps.

[0030] A certain mass of xylitol crystal particle product is prepared, and according to the particle size and particle size distribution characteristics of the xylitol crystal particle product, a metal sieve of 500 microns to 600 microns is selected, and the mass of each particle size range is measured, and the particle number of the crystal particles in each particle size range is statistically calculated, and the equivalent particle radius R is calculated according to formula (e) and formula (f). e is 550 microns. The moisture absorption characteristics of the crystal particle product are measured by a dynamic vapor adsorption device, and the moisture absorption characteristics file of the crystal particle product at a temperature of 25°C shown in Figure 2(a) is obtained. As is clear from Figure 2(a), the deliquescence point of xylitol crystal particles is about 75%, and therefore the high humidity condition of the critical solidification cycle experiment of xylitol crystal particles must be set to 75% or less. In this example, the equivalent particle radius is 550 microns, the temperature is 25°C, and the high and low humidity cycle condition of the storage environment is 65% to 30%, and the critical solidification cycles of various environmental high and low humidity cycles, such as 65% to 30%, 60% to 30%, 55% to 30%, and 50% to 30%, of crystal particles with other equivalent particle radii, such as 312 microns, 404 microns, 507 microns, and 550 microns, are predicted and obtained, and compared with the actual measurement results of the critical solidification cycle to explain the prediction accuracy of the method of the present invention.

[0031] In this embodiment, the critical solidification period is predicted as follows. First, the amount of moisture absorbed V of a crystal grain with an equivalent particle radius of 550 microns under various humidity conditions is measured by a dynamic vapor adsorption apparatus. RHThe crystal particles are selected using a metal sieve of 500 to 600 microns. As shown in FIG. 2(a), at a humidity of 30%, the moisture absorption amount V RH is 0.02000%, and under 50% humidity conditions, the moisture absorption amount V RH is 0.02740%, and under 55% humidity conditions, the moisture absorption amount V RH is 0.03266%, and under 60% humidity conditions, the moisture absorption amount V RH is 0.03747%, and under 65% humidity conditions, the moisture absorption amount V RH The crystal grain product was then filled into a consolidation mold and placed in a temperature and humidity box, and the humidity conditions in the temperature and humidity box were set to 65% to 30% high and low humidity alternating cycles. The critical consolidation period N was measured and found to be 7 times.

[0032] Next, the critical solidification period is calculated and predicted by a formula. The obtained parameters are input into the CHS crystal bridge growth model database, and the formula (g):V RH / V RH '=R e / R e The moisture absorption amount (i.e., HS file) of crystal particle products with various equivalent particle radii under the same humidity condition was calculated by the above method, and the calculation results are shown in Table 1 below. For example, for a crystal particle with an equivalent particle radius of 312 microns, at 30% humidity, its moisture absorption amount V RH is 0.01135%, and under 50% humidity conditions, the moisture absorption amount V RH is 0.01554%, and under 55% humidity conditions, the moisture absorption amount V RH is 0.01853%, and under 60% humidity conditions, the moisture absorption amount V RH is 0.02126%, and under 65% humidity conditions, the moisture absorption amount V RH is 0.02607%. The results of calculations of the moisture absorption amount of crystal particles with other equivalent particle radii such as 404 microns and 507 microns in various humidity environments are shown in Table 1 below.

[0033] [Table 1]

[0034] Furthermore, the equivalent particle radius R 1e It is known that for a crystal grain of 550 microns, the critical consolidation period N1 corresponding to the 65% to 30% environmental high and low humidity cycle conditions is 7 times. The obtained parameters were input into the CHS crystal bridge growth model database, and the formula (a): N1 / N1' = (R 1e / R 1e ') 4 Under the same humidity RH condition, the equivalent particle radius R 1e Calculate the critical solidification period N1' (i.e. CS file) corresponding to the crystal grain of ', and take an integer for the critical solidification period. For example, for a grain with an equivalent grain radius of 312 microns, the critical solidification period N1' corresponding to the 65%-30% humidity cycle condition is 1 time, for a grain with an equivalent grain radius of 404 microns, the critical solidification period N1' corresponding to the 65%-30% humidity cycle condition is 2 times, and for a grain with an equivalent grain radius of 507 microns, the critical solidification period N1' corresponding to the 65%-30% humidity cycle condition is 5 times.

[0035] The above HS file and formula (c): V l =V RH2 -V RH1 The difference in moisture absorption V under conditions where the crystal particles are subjected to one environmental high and low humidity cycle is l , and the moisture absorption difference V of a crystal particle with an equivalent particle radius of 550 microns l The data was calculated, and the moisture absorption difference V of crystal grains with other equivalent particle radii under various environmental high and low humidity cycle conditions was also calculated. l The data was calculated and the results are shown in Table 2 below.

[0036] [Table 2]

[0037] The difference in moisture absorption V under environmental high and low humidity cycle conditions for crystal particles with each of the above equivalent particle radii l and CS files together, equation (b): N2 / N2''=V l ' / V lThe critical solidification period N2'' (i.e., CH file) of the crystal grain product with the same equivalent particle radius under various environmental high and low humidity cycle conditions is calculated, and integers are taken for the calculated critical solidification period. The calculation results are shown in Table 3. For example, for a crystal grain with an equivalent particle radius of 550 microns, the moisture absorption difference V l The data for (65%~30%) is 0.02595, and it is known that the critical consolidation period N2 is 7 times under 65%~30% high and low humidity cycle environmental conditions. According to Table 2, V l The data for '(60%~30%) is 0.01747. As a result of calculation using formula (b), the critical solidification period N2'' of the crystal grains under the 60%~30% high and low humidity cycle condition is 10 times. Similarly, calculate the critical solidification period N2'' under other conditions.

[0038] [Table 3]

[0039] By combining the data from each of the above files, a fitted graph was obtained to predict the critical caking period of the xylitol multi-crystal particle product under various environmental high- and low-humidity cycle storage conditions, as shown in Figure 3.

[0040] Next, the actual measurement results and predicted values ​​of the critical solidification period are verified. A certain mass of xylitol crystal particle product is prepared, and according to the particle size and particle size distribution characteristics of the crystal particle product, it is sorted with metal sieves of 200 microns to 300 microns, 300 microns to 400 microns, and 400 microns to 500 microns, and the median radius corresponding to the particle size ranges is 250 microns, 350 microns, and 450 microns, respectively. After sorting, the crystal particle mass for each particle size range is measured, and when the mass ratio is approximately 1:1:1, the equivalent particle radius R eis 312 microns. Then, the moisture absorption amount of the crystal particle product at humidity of 50%, 55%, 60%, and 65% is measured by a dynamic vapor adsorption device, and in the critical solidification cycle experiment, the environmental high and low humidity cycle conditions are set to 65% to 30%, 60% to 30%, 55% to 30%, and 50% to 30%, respectively, and the critical solidification cycle is measured. Similarly, crystal particles with equivalent particle radii of 404 microns and 507 microns are selected, and then, the moisture absorption amount of the crystal particle product at humidity of 50%, 55%, 60%, and 65% is measured by a dynamic vapor adsorption device, and in the critical solidification experiment, the environmental high and low humidity cycle conditions are set to 65% to 30%, 60% to 30%, 55% to 30%, and 50% to 30%, respectively, and the critical solidification cycle is measured. The measured data of the critical solidification cycle is recorded.

[0041] As shown in Figure 2(b), the moisture absorption amount of crystal particles with equivalent particle radii of 312 μm, 404 μm, 507 μm, and 550 μm at humidity of 50%, 55%, 60%, and 65% increases linearly with the crystal particle size, as shown in formula (g): V RH / V RH '=R e / R e The fitting with the predicted results by ' was good. Under the humidity conditions of 50%, 55%, 60% and 65%, the fitting correlation coefficients were 0.9966, 0.9896, 0.9982 and 0.9974, respectively, which are above 0.98, so the fitting effect was good.

[0042] As shown in Fig. 2(c), the moisture absorption amount is inversely proportional to the critical solidification period, as expressed by equation (b): N2 / N2''=V l ' / V l The fitting is good with the predicted results by the method. When the equivalent particle sizes are 311 μm, 404 μm, 507 μm and 550 μm, the fitting correlation coefficients are 0.9052, 0.9703, 0.9619 and 0.9578, respectively, which are above 0.90, and the fitting effect is good.

[0043] As shown in Fig. 2(d), the grain size is related to the critical solidification period by a fourth power function, as shown in the formula (a): N1 / N1'=(R 1e / R 1e ') 4 The fitting correlation coefficients for the 50%, 55%, 60%, and 65% high humidity cycle conditions are 0.9767, 0.9679, 0.9035, and 0.9011, respectively, which are greater than 0.90, and the fitting effect is good.

[0044] Therefore, by using the CHS crystal bridge growth model database of the present invention to predict the critical solidification period of polycrystalline grain sizes under various environmental high and low humidity cycle conditions, it has the characteristics of accurate prediction effect, small experimental amount, and fast prediction speed.

[0045] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A method for predicting a critical solidification period of a crystal grain, comprising the steps of: First, a CHS crystal bridge growth model database of crystal particles of the same type as the prediction target crystal particle is created, the database including data on equivalent particle radii corresponding to various particle size standards of crystal particles, data on moisture absorption amounts of crystal particles of various equivalent particle radii under various environmental temperatures and various environmental humidity conditions, and data on critical solidification periods of crystal particles of various equivalent particle radii under various environmental temperatures and various environmental high-low humidity cycle conditions; then, according to the equivalent particle radius, storage environmental temperature, and environmental high-low humidity cycle conditions of the prediction target crystal particle, existing data is selected from the corresponding CHS crystal bridge growth model database, and the critical solidification period is calculated according to the following calculation formula, and a predicted critical solidification period for this crystal particle is obtained as a calculation result: The formula includes the following: (1) When the environmental temperature and environmental high-low humidity cycle conditions of the prediction target crystal grain are the same as the data in the CHS crystal bridge growth model database, and only the equivalent particle radius is different, the critical solidification period N of the prediction target crystal grain under the environmental conditions is calculated by the following formula (a): 1 ', N 1 / N 1 '=(R 1e / R 1e ') 4 , Formula (a) In the above formula, R 1e is the equivalent grain radius of the crystal grains existing in the CHS crystal bridge growth model database, and R 1e ' is the equivalent particle radius of the predicted target crystal grain, and N 1 is the equivalent particle radius R 1e is the critical solidification period of the crystal grains corresponding to the environmental conditions, and N 1 ' is the critical solidification period of the predicted crystal grain, and N 1 and N 1 ' are integers of 1 or more, (2) When the environmental temperature and equivalent particle radius of the prediction target crystal grain are the same as those in the CHS crystal bridge growth model database, and only the environmental high-low humidity cycle conditions are different, the critical solidification period N of the prediction target crystal grain can be calculated by the following formula (b). 2 Calculate `` N 2 / N 2 ''=V l ' / V l 、 Formula (b) Where: V l = V RH2 - V RH1 、Equation (c) V l ’ = V RH3 - V RH1 、Equation (d) In the above formula, V RH2 is the amount of moisture absorbed under high humidity conditions in the first environmental high and low humidity cycle of a crystal grain existing in the CHS crystal bridge growth model database, and V RH3 is the moisture absorption amount of the crystal grains existing in the CHS crystal bridge growth model database under high humidity conditions in the second environment high and low humidity cycle, and the low humidity conditions in the first environment high and low humidity cycle and the second environment high and low humidity cycle are the same; V RH1 is the amount of moisture absorbed under low humidity conditions in the high and low humidity cycle of the crystal grains existing in the CHS crystal bridge growth model database, and V l is the difference in moisture absorption amount of the crystal particles under the first environmental high and low humidity cycle condition, and V l ' is the difference in moisture absorption amount of the prediction target crystal grain under the second environmental high and low humidity cycle conditions, and N 2 is the critical solidification period of the crystal grains existing in the CHS crystal bridge growth model database under the first environmental high and low humidity cycle conditions, and N 2 '' is the critical solidification period of the prediction target crystal grain under the second environmental high and low humidity cycle condition, and N 2 and N 2 '' are each an integer of 1 or greater, A method for predicting the critical solidification period of crystal particles, characterized in that the high humidity condition in the environmental high and low humidity cycle is lower than the deliquescence point of the crystal particles, the critical solidification period when the particle diameter of the crystal particles is less than 100 microns is greater than one, the low humidity condition is lower than the high humidity condition, and the humidity difference between the two is greater than 20%.

2. The equivalent particle radius of the crystal grain in the CHS crystal bridge growth model database and the equivalent particle radius of the prediction target crystal grain are, respectively, First, the grain size of the crystal grain product to be measured is selected, and then the mass of the crystal grains for each grain size range is measured, and the data m 1 , m 2 , …, m n At the same time, the number of crystal grains in each grain size range is counted, and the data P 1 , P 2 , …, P n Then, the equivalent particle radius R of the crystal grain is calculated by the following formula: e The formula is: P 1 R 1 3 +P 2 R 2 3 +…+P n R n 3 =(P 1 +P 2 +…+P n ) e 3 , formula (e) P 1 R 1 3 :P 2 R 2 3 :…:P n R n 3 = m 1 :m 2 :…:m n 2. The method for predicting the critical solidification period of crystal grains according to claim 1, further comprising the following formula (f):

3. The critical solidification period of the crystal grains having various equivalent particle radii at various environmental temperatures and various environmental high and low humidity cycles is 2. The method for predicting the critical solidification period of crystal particles according to claim 1, characterized in that: first, a crystal particle product to be measured is filled into a consolidation mold and placed in a box with a set temperature; the high and low humidity of the high and low humidity cycle in the box are set to match the environmental high and low humidity cycle of the crystal particles to be measured; the period of the high and low humidity cycle is set to 12 to 24 hours; then, timing of the high and low humidity cycle is started; each time a high and low humidity cycle period is completed, the solidified body in the consolidation mold is released; if the solidified body of the crystal particles collapses upon release, it is determined that the crystal particle product is not solidified; the cycle is continued until the next period; when the solidified body of the crystal particles no longer collapses, the number of periods until the solidified body no longer collapses is recorded, and this is regarded as the critical solidification period of the crystal particles under the environmental temperature and environmental high and low humidity cycle conditions.

4. 4. The method for predicting the critical solidification period of a crystal grain as described in claim 3, characterized in that, when measuring the critical solidification period, the critical solidification period is measured three times, and the average value of the critical solidification periods measured three times is used as the averaged critical solidification period.

5. V in formulas (c) and (d) RH1 , V RH2及び V RH3 is also calculated by the following method: Under the conditions of the same environmental temperature, the same environmental humidity, and different equivalent particle radii, the equivalent particle radius R is calculated by the following formula (g). e The amount of moisture absorbed by the crystal particles of V under the environmental humidity RH conditions RH ', V RH / V RH ' = R e / R e ', formula (g) In the above formula, V RH is the equivalent particle radius R e is the amount of moisture absorbed by the crystal particles under environmental humidity RH conditions, and V RH ' is V RH1 , V RH2 and V RH3 2. The method for predicting the critical solidification period of crystal grains according to claim 1, wherein the critical solidification period corresponds to any one of the following:

6. The method for predicting the critical solidification period of crystal particles as described in claim 1, characterized in that the moisture absorption amount of crystal particles is measured using a dynamic vapor adsorption device, an initial drying process is performed on the crystal particle sample to be measured prior to the measurement, and the mass of the crystal particle sample to be measured is 10 mg or less.

7. 2. The method for predicting the critical solidification period of crystal grains according to claim 1, wherein in the environmental high and low humidity cycle of the crystal grains, the high humidity condition is 65% and the low humidity condition is 30%.

Citation Information

Patent Citations

  • Rapid caking and measuring method for salt sample

    CN105784480A

  • Quantitative characterization method for moisture absorption and agglomeration degree of powder

    CN107063906A

  • A method for predicting the coalescence rate and coalescence strength of crystals under hygroscopicity

    CN108959817A

  • Synchronous measurement system and measurement method for particle size and mass moisture absorption growth of atmospheric particulates

    CN114965186A

  • Measuring equipment and method for moisture absorption and releasing property

    JP2004157086A